2019
DOI: 10.1098/rspb.2019.2290
|View full text |Cite
|
Sign up to set email alerts
|

Temporally varying disruptive selection in the medium ground finch (Geospiza fortis)

Abstract: Disruptive natural selection within populations exploiting different resources is considered to be a major driver of adaptive radiation and the production of biodiversity. Fitness functions, which describe the relationships between trait variation and fitness, can help to illuminate how this disruptive selection leads to population differentiation. However, a single fitness function represents only a particular selection regime over a single specified time period (often a single season or a year), and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…While this is simpler than the original analysis [51], we have found that temperature may affect both survival and bill size. The opposing trends of rainfall and temperature that we find in bill surface area could indicate that the morphs are using different thermoregulatory strategies [56] big morphs can use their beaks for effective radiative thermoregulation even when temperatures are high, whereas small morphs cannot, thus leading to higher survival of the big morphs in hot years.…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…While this is simpler than the original analysis [51], we have found that temperature may affect both survival and bill size. The opposing trends of rainfall and temperature that we find in bill surface area could indicate that the morphs are using different thermoregulatory strategies [56] big morphs can use their beaks for effective radiative thermoregulation even when temperatures are high, whereas small morphs cannot, thus leading to higher survival of the big morphs in hot years.…”
mentioning
confidence: 84%
“…Additionally, climatic warming is not always discussed even when temperature is the focus: Studies looking to verify Allen's rule can, while verifying the link to temperature, leave out the temporal trend associated with climate change, despite data spanning meaningful time frames of several decades (e.g., [16,44,50]). Some studies in recent years have explicitly tested for morphological changes over time, but they have been more focussed on the role of different proximal factors, such as diet, or other aspects of anthropogenic disturbance and climate change [51,52] (Box 1).…”
Section: The Hidden Role Of Climate Change In Causing Morphological Changementioning
confidence: 99%
See 2 more Smart Citations
“…Simpson (7) later described the phenotypic evolution of populations through time on a rugged landscape, in which isolated clusters of fitness peaks represent 'adaptive zones' to which populations evolve from adjacent regions of low fitness (8). Lande and Arnold formalized the analysis of selection and estimation of phenotypic fitness landscapes (9)(10)(11), leading to empirical studies of fitness landscapes in numerous empirical systems (12)(13)(14)(15)(16)(17)(18). Fitness surfaces also provide a central component of speciation models and theory (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%